IMPLIKASI PERAN PENDIDIKAN KEWARGANEGARAAN TERHADAP PENERAPAN PERLINDUNGAN HAK CIPTA - Nuryadi, Muhammad Hendri (PKn Progresif, 2015)
Copyright is the part of other rights, the regulation of which exists in law science called Intellectual Property Right. Copy right is the one of a creation?s author to his/her creation and copy. The author of a creation has full right to his/her creation and copy of his/her creation. This right included the one to make copy of his/her creation, of developing derivative product, and of transferring the right to others. Copyright prevails as soon as the creation is made. Copyright is unnecessary to be registered first. In fact in the field there are many breaches to this copyright so that a means is required to minimize this breach through the role of education, particularly Civic Education aiming to create a good citizen, the one Knowing (Cognitive), Willing (Affective) and Able to do (Psychomotor) everything becoming his/her right and obligation as a Citizen.